Qonun in Indonesia from an Ontological and Axiological Review - Sholihin Shobroni (IRDH International Journal of Social Sciences & Humanities, 2024)
Applying Qonun to various products in Indonesia has resulted in multiple legal products. However, its implementation still reaps the pros and cons in the public. The purpose of this research is to convey the implementation of Qonun from the Ontological and Axiological reviews. The research method used is descriptive, with literature review data analysis. The implementation of Qonun in Indonesia has been ongoing since the beginning of the independence of the Republic of Indonesia. The implementation of Qonun has been realized in various legal products including Laws, Government Regulations, Presidential Instructions, and Regional Regulations. Thus, the implementation of Qonun can be reviewed to fulfill the Ontological and Axiological aspects.